CONSUMER BEHAVIOR: CONFIDENCE RELATIONSHIPS AND CONFORMITY WITH CONSUMTIVE BEHAVIOR ONLINE SHOPPING FASHION PRODUCTS USERS INSTAGRAM APPLICATIONS - Nungky Irma Triyanti; Usman Effendi (JMB : Jurnal Manajemen dan Bisnis, 2017)
The focus of this research on consumptive behavior is human action in an effort to fulfill the necessity of life, where most of the students to fulfill the necessities of life still depend on the assistance of parents. Therefore, in measuring consumer behavior used confidence and conformity as a parameter. The population of this research is a student of one private university in Jakarta who is considered to represent as a student community. The method used is descriptive method. Data collection methods used questionnaires with Likert scale models on the three variables of confidence, conformity and consumptive behavior. Based on multiple regression analysis obtained value of R2 equal to 0,379 with p<0,05. So it can be concluded that there is a significant relationship between self-confidence and conformity with consumptive behavior of online shopping fashion products on the students application Instagram means that confidence and conformity contributes 37.9% towards consumptive behavior. Among self-confidence accounted for 28.2% while conformity accounted for 9.7% of consumer behavior consumptive shopping online fashion products on application students Instagram applications.Fokus penelitian ini pada perilaku konsumtif adalah tindakan manusia dalam upaya memenuhi kebutuhan hidup, di mana sebagian besar siswa untuk memenuhi kebutuhan hidup masih bergantung pada bantuan orang tua. Oleh karena itu, dalam mengukur perilaku konsumen digunakan kepercayaan dan kesesuaian sebagai parameter. Populasi penelitian ini adalah mahasiswa dari satu universitas swasta di Jakarta yang dianggap mewakili sebagai komunitas mahasiswa. Metode yang digunakan adalah metode deskriptif. Metode pengumpulan data menggunakan kuesioner dengan model skala Likert pada tiga variabel kepercayaan, konformitas dan perilaku konsumtif. Berdasarkan analisis regresi berganda diperoleh nilai R2 sebesar 0,379 dengan p <0,05. Jadi dapat disimpulkan bahwa ada hubungan yang signifikan antara kepercayaan diri dan konformitas dengan perilaku konsumtif dari produk belanja online fashion pada aplikasi siswa Instagram berarti bahwa kepercayaan dan konformitas menyumbang 37,9% terhadap perilaku konsumtif. Di antara kepercayaan diri menyumbang 28,2% sementara konformitas menyumbang 9,7% dari perilaku konsumen belanja online konsumtif produk fashion pada aplikasi aplikasi Instagram siswa.